Editorial Comments - Vance, Stanley (Academy of Management Journal, 1969)
The author reports on the correlation between mobility and management theory, with a particular example of a university professor travelling across the country and seeing co-workers at airports. The development of modes of transportation is noted as a product of human progress and civic development. The management mobility model is introduced to represent the level of progress and an event's significance in the field of management. The model accounts for the number of attendees, distance travelled, length of meeting, total time, and related trip objectives. The author concedes to be quantifying the immeasurable, but the purposes behind professionals' travel are not equal.